Implementasi Metode Defragmenting pada Mata Pelajaran Estimasi Biaya Konstruksi untuk Meningkatkan Kemampuan Analisis Siswa : Penelitian - Alfisyah Rahmawati; Sutrisno; Retno Dyah Hastuti; Afidya Eriska Musdiyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to examine the effectiveness of implementing the defragmenting method in learning Construction Cost Estimation (CCE) in class XI DPIB 1 at SMK Negeri 1 Singosari. The research background is based on the complexity of CCE material that demands high analytical skills, while many students still have difficulties in analogizing formulas, converting units, understanding basic cost concepts, and planning budgets. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that the defragmenting method, which consists of the stages of identifying errors in the structure of thinking, scaffolding review, conflict cognitive, and disequilibration, was able to map and improve students' analytical skills significantly. The average score of student activities increased from the